Quantitative Elastography of the Cervix for Predicting Labor Induction Success - Fruscalzo, A.; Londero, A. P.; Fröhlich, C.; Meyer-Wittkopf, M.; Schmitz, R. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To evaluate the role of quantitative elastography of the cervix in the prediction of successful labor induction compared to the Bishop score (BS) and ultrasound cervical length (CL).Materials and Methods: A prospective pilot study was conducted between July 2010 and June 2011 in patients without preterm membrane rupture undergoing labor induction with vaginal prostaglandins. Before starting induction, the BS, functional CL and cervical tissue strain (TS) were assessed. TS assessment was performed twice using the Tissue Doppler Imaging (TDI) software. Diagnostic accuracy was evaluated for the prediction of the following endpoints: active labor achievement (success vs. failure, time interval < 24 h and < 48 h), vaginal delivery (success vs. failure, time interval < 36 h and < 72 h) and total amount of prostaglandins used for labor induction (< 6 mg and < 12 mg).Results: We analyzed 77 patients with a mean gestational age of 39.7 ± 1.5 weeks of gestation and a mean strain of 0.75 ± 0.17. The TS significantly predicted a failure of labor induction, which occurred in 4 cases, both in mono- and multivariate analysis, independently of the functional cervical length (TS 0.6 ± 0.1). No correlation was found between the TS and other outcomes. The Bishop score and functional cervical length were found to predict only an early response to labor induction (time to active labor < 24 h, time to vaginal delivery < 36 h and PG usage < 6 mg). The diagnostic accuracy was slightly but not significantly improved if both TS and CL were considered.Conclusion: Preliminary data show the possible usefulness of quantitative cervical elastography in the prediction of labor induction failure.
Keywords: cervix; ultrasound Doppler; obstetrics; tissue elastography; tissue doppler imaging; labor induction; sensitivity and specifity